2008
DOI: 10.1523/jneurosci.4334-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Necdin Plays a Role in the Serotonergic Modulation of the Mouse Respiratory Network: Implication for Prader-Willi Syndrome

Abstract: Prader-Willi syndrome is a neurogenetic disease resulting from the absence of paternal expression of several imprinted genes, including NECDIN. Prader-Willi children and adults have severe breathing defects with irregular rhythm, frequent sleep apneas, and blunted respiratory regulations. For the first time, we show that Prader-Willi infants have sleep apneas already present at birth. In parallel, in wild-type and Necdin-deficient mice, we studied the respiratory system with in vivo plethysmography, in vitro e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 57 publications
10
84
1
4
Order By: Relevance
“…Several knockout models of Ndn have been reported with different phenotypic outcomes ranging from early postnatal lethality owing to respiratory distress to normal viability (Gérard et al 1999, Muscatelli et al 2000, Kuwako et al 2005. Ndn knockout mice variously demonstrate hypothalamic changes, including reduced numbers of oxytocin-and LHRH neurons (Muscatelli et al 2000), more generalised defects in neuronal differentiation (Kuwako et al 2005, Kuwajima et al 2006) and abnormally high levels of serotonin in the medulla (Zanella et al 2008). Necdin is also implicated in axonal outgrowth, routing and fasciculation, thereby possibly participating in establishment of neuroendocrine circuits .…”
Section: Studies Of Imprinted Gene Function In the Hypothalamusmentioning
confidence: 99%
“…Several knockout models of Ndn have been reported with different phenotypic outcomes ranging from early postnatal lethality owing to respiratory distress to normal viability (Gérard et al 1999, Muscatelli et al 2000, Kuwako et al 2005. Ndn knockout mice variously demonstrate hypothalamic changes, including reduced numbers of oxytocin-and LHRH neurons (Muscatelli et al 2000), more generalised defects in neuronal differentiation (Kuwako et al 2005, Kuwajima et al 2006) and abnormally high levels of serotonin in the medulla (Zanella et al 2008). Necdin is also implicated in axonal outgrowth, routing and fasciculation, thereby possibly participating in establishment of neuroendocrine circuits .…”
Section: Studies Of Imprinted Gene Function In the Hypothalamusmentioning
confidence: 99%
“…Alternately, increased appetite may be secondary to abnormal expression of non-ghrelin genes. For instance, it has recently been suggested that genes involved in the development of serotoninergic pathways are affected in PWS, which could potentially influence appetite (24,25). Finally, while Oct decreases plasma concentrations of ghrelin, an orexigenic hormone, it also decreases the concentrations of anorexigenic hormones, such as insulin (26) and PYY (27).…”
Section: Discussionmentioning
confidence: 99%
“…La création de modèles de souris transgéniques a incité également les chercheurs à adapter l'approche de Suzue à la souris, afin d'étudier in vitro le développement du CPB de souris dont un gène et un seul a été inactivé. Couplées à des approches pharmacologiques, ces études ont révélé que les systèmes à sérotonine (5-HT) [15,16] et à catécholamine [17,18] modulent le fonctionnement du CPB, et que l'altération de ces systèmes affecte la maturation de ce dernier [19][20][21]. À Gif-sur-Yvette (France), l'utilisation combinée de l'électrophysiologie et de l'imagerie calcique in vitro a révélé que l'émer-gence fonctionnelle du CPB est précédée par celle du groupe rétrotrapézoïde/parafacial (RTN/pFRG), une structure cruciale pour la réponse respiratoire à l'hypercapnie chez l'adulte.…”
Section: Rôle Crucial Du Complexe De Pré-bötzinger Dans L'automatismeunclassified
“…En effet, la maturation et le fonctionnement du CPB sont modulés par les systèmes monoaminergiques [15][16][17][18][19][20][21] ; les gènes qui modifient ces systèmes affectent indirectement le CPB. Ainsi, l'inactivation chez la souris de l'enzyme MAOA-A (monoamine oxydase A) [15] ou du gène Phox2a (paired mesoderm homeobox protein 2A) [17] ou du gène c-Ret (rearranged during transfection) [18] altère les systèmes monoaminergiques et, par voie de conséquence, le CPB et la respiration ; des anomalies monoaminergiques pourraient contribuer à certains cas de mort subite du nourrisson [16,[19][20][21]. L'inactivation du gène Necdin, qui affecte les systèmes à 5-HT, induit un rythme respiratoire irrégulier, de fréquentes apnées et une hyposensibilité à l'hypoxie et l'hypercapnie.…”
Section: Aspects Cliniquesunclassified
See 1 more Smart Citation